Physical Properties and Lipid Bioavailability of Nanoemulsion-Based Matrices with Different Thickening Agents - Arancibia-Aguilar, C; Miranda-Sandoval, M; Matiacevich, S (Elsevier B.V., 2017)
This work studies the influence of two thickening agents, starch and carboxymethyl cellulose (CMC) with different structural characteristics on physical properties and lipid bioavailability of avocado oil-based nanoemulsions. Eight nanoemulsions were prepared varying oil content (5 and 15%) and thickener type and concentration (CMC: 0.5–0.75%; Starch: 6–8%). Particle size (PS) and zeta potential (ZPot) depended mainly on the thickener type; starch-based nanoemulsions showed a lower PS and ZPot values near to zero. Nanoemulsions containing the highest oil (15%) and thickener concentrations (0.75% CMC or 8% starch) were more viscous and pseudoplastic than those with 5% oil. With respect to physical stability, the CMC-thickened nanoemulsions exhibited a better stability than starch-based samples. Starch-based nanoemulsions with 15% oil showed the highest creaming index values (40–45%) after 21 days of storage. In turn, the hydrocolloid type had a significant (p < 0.05) effect on lipid bioavailability of O/W nanoemulsions. Nanoemulsions with 5% and 15% oil did not show significant differences on the digestion rate due to thickener type. However, nanoemulsions with 15% oil presented lower digestion rates and final extent of free fatty acids released, with a lag time increased. At 15% oil, CMC-based nanoemulsions showed a lower release of free fatty acids after lipolysis than starch-thickened samples, indicating that CMC caused physical retention of oil droplets in the matrix structure, delaying lipid digestion. © 2017 Elsevier Ltd